A Novel E-DVA Module Synthesis Featuring of Synergy between Driving and Vibration Attenuation. (25th August 2016) - Gu, Cheng; Zhu, Jianfei; Chen, Xinbo
Abstract : To attenuate the negative effects brought by heavy unsprung mass of the decentralized driving electric vehicle, a novel e-DVA module featuring of synergy between driving and vibration attenuation is proposed in this paper. It presents the advantages of compact structure and low cost. Structure design proves the feasibility of the e-DVA module. Kinematic analysis of the slider-crank mechanism is carried out to conclude the transmission ratio ripple under road excitation. After parameter matching and optimization of the e-DVA module based on theH 2 / H ∞ norm criterions, vertical dynamics analyses in both frequency and time domains are conducted theoretically to prove the performance improvements on the ride comfort and handling stability under the constraint of DVA deflection bound.